2007
DOI: 10.1038/sj.ki.5002028
|View full text |Cite
|
Sign up to set email alerts
|

Uremia-related vascular calcification: More than apatite deposition

Abstract: In the present study, we characterized and compared the mineral phase deposited in the aortic wall of two different frequently used chronic renal failure rat models of vascular calcification. Vascular calcification was induced in rats by either a 4-week adenine treatment followed by a 10-week high-phosphate diet or 5/6 nephrectomy followed by 6 weeks of 0.25 microg/kg/day calcitriol treatment and a high-phosphate diet. Multi-element mapping for calcium and phosphate together with mineral identification was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
62
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 33 publications
3
62
1
Order By: Relevance
“…With synchrotron radiation analysis, however, because of the combination of micrometer resolution and short acquisition times (a few seconds), a more systematic scanning of the sample covering a larger area can be obtained, which is a major advantage of this technique-albeit at the cost of a lower resolution when compared with high-resolution TEM techniques. To the best of our knowledge, only Verberckmoes et al 10 applied synchrotron radiation analysis to examine vascular calcifications in rats with uremia, in which they also identified whitlockite as an important component of the mineral phase, particularly in vitamin D-treated animals. No studies using synchrotron radiation for diffraction analysis of human vascular calcification have been reported so far.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With synchrotron radiation analysis, however, because of the combination of micrometer resolution and short acquisition times (a few seconds), a more systematic scanning of the sample covering a larger area can be obtained, which is a major advantage of this technique-albeit at the cost of a lower resolution when compared with high-resolution TEM techniques. To the best of our knowledge, only Verberckmoes et al 10 applied synchrotron radiation analysis to examine vascular calcifications in rats with uremia, in which they also identified whitlockite as an important component of the mineral phase, particularly in vitamin D-treated animals. No studies using synchrotron radiation for diffraction analysis of human vascular calcification have been reported so far.…”
Section: Discussionmentioning
confidence: 99%
“…These previous studies used different tissues and yielded different results: Hydroxyapatite [Ca 10 (PO 4 ) 6 OH 2 ]-as seen in the skeleton-was described as the sole mineral phase of uremic arterial calcifications in two studies, 7,8 whereas another study found both brushite and hydroxyapatite in calcifications of stenotic arteriovenous fistulas. 9 In a rodent study of uremic calcification, whitlockite, a magnesium-containing crystal [(Ca,Mg) 3 (PO 4 ) 2 ], was detected in addition to hydroxyapatite.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the accompanying The increase in phosphate levels predisposes to the precipitation of calcium phosphate crystals in the media of the walls of the vessels. (18,19) In an elegant study on the rat model, Verberckmoes et al found calcium phosphate and whitlockite crystals in the aortas of uraemic animals.…”
Section: Bone-mineral Disorder (Bmd)mentioning
confidence: 99%
“…16 However, we did not observe significant reversal of calcification after aortic transplantation in an animal model of this disorder. 17 Vascular calcifications are composed primarily of apatitic mineral with varying amounts of whitlockite, 18,19 both of which are highly insoluble under physiological conditions 20 and thus are not expected to disappear spontaneously. Apatite appears not to form spontaneously from calcium and phosphate ions, whereas initially brushite (CaHPO 4 2H 2 O) and/or other intermediates (including amorphous calcium phosphate) that are more soluble may be present in variable amounts in calcified vessels.…”
mentioning
confidence: 99%